The Strategic analysis cycle handbook : how advanced data collection and analysis underpins winning strategies - Elgersma, Erik. (London, United Kingdom : LID, 2017)
This is an authoritative and practical guide to collecting, analyzing and managing data, to enable managers and companies to develop successful business strategies. Data has become a dominant factor in today$1 (Bs business environment. This book, written by a leading practitioner, explains the underpinning nature of data for a company$1 (Bs business strategy. The book begins with data collection: getting data is no big deal; getting the right data to win in the market is. It moves on to data analysis: turning data into actionable intelligence is what drives and determines competitive advantage. And, finally, managing data: how to organize your data collection and analysis to create winning strategies. This is a definitive book about one of the most important topics in today$1 (Bs digital and data-driven economy.s
Chapter 1. Introduction -- 2. Briefing and project brief -- 3. Attributes of sources and the collection plan -- 4. People: Collection from friendly or neutral sources -- 5. People: collection from unsuspecting sources -- 6. Papers: Collection from Public domain sources -- 7. Pictures: Collection of data from images -- 8. Products of data from things -- 9. Analysis -- 10. Input data quality assurance -- 11. Data-set preparation -- 12. Common issues in data set processing -- 13. Hypothesis formulation and testing -- 14. Analytical pitfalls -- 15. Reporting -- 16. Analyst decision-maker interaction -- 17. Social biases in decision-making -- 18. Ethics and compliance in data collection -- 19. Data management and retrieval -- 20. Organizing a strategic analysis function -- 21. Profile of a strategy analyst.
Includes bibliographical references.
Keywords: BUSINESS CYCLES